Evolution of the Journal and the Field of Organization Design - John Joseph (Journal of Organization Design, 2018)
This commentary reflects on how the themes in the Journal of Organization Design have evolved along with the field of organization design itself. Using topic modeling of abstracts, I assess the key topics or themes in the Journal of Organization Design and compare them to themes underlying design studies in mainstream management journals. I propose some mechanisms behind the differences and similarities and offer some implications for the future of the journal.
Keywords: 650; Founders' imprinting; Journal of Organization Design; Organizational goals; Topic models